Humic Acid Modified by Being Incorporated Into Phosphate Fertilizer Increases Its Potency in Stimulating Maize Growth and Nutrient Absorption - Jing, Jianyuan; Zhang, Shuiqin; Yuan, Liang; Li, Yanting; Chen, Chengrong; Zhao, Bingqiang (Frontiers in Plant Science, 2022)
Humic acid-enhanced phosphate fertilizer (HAP) is widely applied in Chinese agriculture due to its high efficiency. Although the structural composition and physicochemical properties of humic acid (HA) are significantly altered during HAP production, a clear understanding of mechanisms underlying the biological effects of HA extracted from HAP fertilizer (PHA) on plant growth is still lacking. In the current study, we extracted PHA from HAP, and assessed its effects on the dry biomass, phosphorus (P) and nitrogen (N) uptake, and P absorption rate of maize seedlings when supplied at different concentrations (2.5, 5, 10, and 25 mg C L-1) in the hydroponic culture. The root vigor and root plasma membrane H+-ATPase activity, and root nitrate reductase activity were also determined as the representative indicators of the root capacity for nutrient absorption, and used to clarify the mechanism of PHA affecting maize growth and nutrient absorption. The results showed that the dry biomass, phosphorus uptake, nitrogen uptake, and average phosphorus absorption rates were significantly higher by 14.7%-27.9%, 9.6%-35.1%, 17.9%-22.4%, and 22.1%-31.0%, respectively in plants treated with 2.5 to 5 mg C L-1 PHA compared to untreated controls. Application of 10 to 25 mg C L-1 raw HA resulted in similar stimulatory effects on plant growth and nutrient absorption. However, higher levels of PHA (10 to 25 mg C L-1) negatively impacted these indicators of plant growth. Furthermore, low PHA or high raw HA concentrations similarly improved root vigor as well as root plasma membrane H+-ATPase and nitrate reductase (NR) activities. These results indicate that lower concentrations of PHA can stimulate maize seedling growth and nutrient absorption to the extent which is comparable to the effect of higher concentrations of raw HA. Thus, the proportion of HA incorporated into HAP could be lower than the theoretical amount estimated through assays of the biological effects of raw HA.